2019
DOI: 10.26637/mjm0703/0008
|View full text |Cite
|
Sign up to set email alerts
|

A study on recruitment and selection process with reference to current scenario in organizations

Abstract: The success of organizations in this modern business environment depends on the performance / strength / caliber of the manpower that steers the day to day affairs of the organizations. The process of recruiting and selecting all categories of employees into both private and public organization has been a matter of concern to many and needs attention. It is the wish of every organization to attract the best human resource in order to fulfill organization needs and got excellent performance by appropriate candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Finally, from the recruitment and selection research, it is concluded that the growth and success of any company depends on the effective work of its employees and therefore it is very important for the organization to select experienced and qualified candidates. The recruitment and selection process requires careful and careful process planning, so great care must be taken when recruiting staff for any organization (Khandelwal & Kumar, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, from the recruitment and selection research, it is concluded that the growth and success of any company depends on the effective work of its employees and therefore it is very important for the organization to select experienced and qualified candidates. The recruitment and selection process requires careful and careful process planning, so great care must be taken when recruiting staff for any organization (Khandelwal & Kumar, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fair, valid, and reliable recruitment and selection processes have been found to improve businesses by aiding decision-making and identifying employee strengths and weaknesses, ultimately contributing to organizational growth. Additionally, effective recruitment and selection processes have a significant influence on workforce quality, overall performance, and employee performance, retention, and overall organizational outcomes (Kumar, et al 2019) (Swamy, et al, 2023).…”
Section: Recruitment and Selection Processmentioning
confidence: 99%